Financial health analysis and prospects of Munchies Deliveries Ltd. in the Bangladesh food delivery market: comparative study and recommendations - Afnan, Minhajul Abedin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.